Politik Perampasan Tanah Global di Indonesia - Asy'ari, Muhammad (Journal of International and Local Studies, 2022)
The global phenomenon of large-scale land acquisition is currently taking place massively in various countries, especially in Global South. The practice of land acquisition is driven by various economic and political interests by global actors which later give rise to the term global land grabbing. This paper aims to describe the stage and political economy context of global land grabbing in Indonesia which is processed from various studies and reports, particularly the dynamics of the context and model of global land grabbing in Indonesia. The results of the study showed that the phenomenon of land grabbing is a global phenomenon that has taken place in various countries, including Indonesia. The history of land grabbing is very close to the colonialization era and the development of global capitalism. Also, it links to the changes in food patterns and the need for an extensive land area to do the transformation of renewable energy and climate change. Historically, the practice of land grabbing in Indonesia has been occurring since the era of colonialism through various methods and policies of large-scale land acquisition using a violent approach